Dental Students' Perceptions of Digital and Conventional Impression Techniques: A Randomized Controlled Trial. Issue 10 (1st October 2017) - Zitzmann, Nicola U.; Kovaltschuk, Irina; Lenherr, Patrik; Dedem, Philipp; Joda, Tim
Abstract : The aim of this randomized controlled trial was to analyze inexperienced dental students' perceptions of the difficulty and applicability of digital and conventional implant impressions and their preferences including performance. Fifty undergraduate dental students at a dental school in Switzerland were randomly divided into two groups (2×25). Group A first took digital impressions in a standardized phantom model and then conventional impressions, while the procedures were reversed for Group B. Participants were asked to complete a VAS questionnaire (0–100) on the level of difficulty and applicability (user/patient‐friendliness) of both techniques. They were asked which technique they preferred and perceived to be more efficient. A quotient of "effective scan time per software‐recorded time" (TRIOS) was calculated as an objective quality indicator for intraoral optical scanning (IOS). The majority of students perceived IOS as easier than the conventional technique. Most (72%) preferred the digital approach using IOS to take the implant impression to the conventional method (12%) or had no preference (12%). Although total work was similar for males and females, the TRIOS quotient indicated that male students tended to use their time more efficiently. In this study, dental students with no clinical experience were very capable of acquiring digital tools, indicating that digital impression techniques can be included early in the dental curriculum to help them catch up with ongoing development in computer‐assisted technologies used in oral rehabilitation.